Social Aspects of Ageing - Selected Challenges, Analyses, and Solutions - Andrzej Klimczuk (IntechOpen, 2024)
Social Aspects of Ageing - Selected Challenges, Analyses, and Solutions, focuses on the key challenges underlined by the United Nations during the Decade of Healthy Ageing (2021-2030). The authors introduce studies in areas crucial for older people, their families, and communities, such as combatting ageism, age-friendly environments, and care provision. The volume also examines issues linked to the global, national, regional, and local implementation of age-specific and intergenerational solutions, initiatives, and programs towards achieving the United Nations Sustainable Development Goals (SDGs). The collection contains chapters representing research and practical recommendations from various disciplines, such as critical studies, geographical gerontology, legal studies, public health, and sociology. This volume is an asset to academic and professional communities interested in theories of ageing as well as public services and ageing policies. In addition, the book aims to help students, practitioners, and people working in government, business, and nonprofit organizations.
Keywords: J14; J18; J10; 330; ageing policy; older people; population ageing; social gerontology; public policy on ageing